Analisis Model Pembelajaran Problem Based Learning dalam Meningkatkan Hasil Belajar Siswa Sekolah Dasar Materi Keberagaman - Hani Risdiany; Indah Cahaya Putri; Putri Salma N; Rani Fitriani; Siti Fatimah; Tuti Istianti (Departement of Mathematics Education, 2022)
This research is a literature study or literature review with a qualitative descriptive approach. Researchers obtained data from several sources such as journals, theses, books, and others that are still relevant to this research study. The instrument in this study was the researcher himself who reviewed some of the results of previous research which were then described in paragraphs. The stages in obtaining research data are starting from reading, analyzing and then concluding. The results showed that the Problem Based Learning model was able to improve the learning outcomes of elementary school students in diversity matters. The existence of giving problems in the diversity material used, is able to spur students to think critically. With the problems given students can provide solutions to their problems according to the findings they find from the various sources they have used. Through discussions to solve problems, students are able to get various answers so that the most appropriate answer can be chosen to solve the problem. With the Problem Based Learning model, student cooperation will be trained so that students are able to improve their critical thinking as a whole.